A high-strength, high-temperature-resistant flexible graphite composite bipolar plate and a preparation method thereof

Biomass carbon modified expanded graphite is produced by synchronous expansion of flexible graphite with carbohydrates, and is impregnated and cured with a high cross-linking density thermosetting resin, which solves the problem that existing bipolar plate materials cannot meet high strength and high toughness at the same time. The problems of high temperature resistance and corrosion resistance have achieved efficient and environmentally friendly bipolar plate preparation.

CN119050396BActive Publication Date: 2025-02-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411506916.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing bipolar plate materials cannot meet the requirements of high strength, high toughness, high temperature resistance and corrosion resistance at the same time, and are difficult to meet the application needs of high-power high-temperature fuel cell stacks.

Method used

The biomass carbon modified expanded graphite is produced by synchronous expansion of flexible graphite with carbohydrates, and a preformed electrode plate is obtained by cold pressing. Then, it is impregnated and cured with a high cross-linking density thermosetting resin to prepare high-strength and high temperature resistance. flexible graphite composite bipolar plate.

Benefits of technology

It realizes the high strength, high temperature resistance, corrosion resistance and high toughness of the bipolar plate, meeting the application needs of high-power high-temperature fuel cell stacks, and at the same time, the process is clean and environmentally friendly, and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119050396B_ABST
    Figure CN119050396B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-strength, high-temperature resistant flexible graphite composite bipolar plate and a preparation method thereof, which belongs to the technical field of high-temperature fuel cell materials. The expanded graphite treated with carbohydrates is impregnated and hot-pressed to obtain a finished bipolar plate. The carbohydrates used in the present invention include but are not limited to biomass components such as starch and maltose. After being configured into an aqueous solution, the expandable graphite is rinsed and dried, and then expanded in an expansion furnace to obtain modified expanded graphite. The process does not involve any toxic, harmful and polluting substances, is clean, environmentally friendly and low-cost, and is suitable for large-scale production. In order to further improve the heat resistance of the bipolar plate, the present invention uses a thermosetting resin with a high cross-linking density for impregnation, and the resin includes but is not limited to bismaleimide resin, furan resin, vinyl ester resin, etc. The bipolar plate prepared based on the method of the present invention has the characteristics of high strength and high temperature resistance, which can meet the application requirements of high-power high-temperature fuel cell stacks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength, high-temperature-resistant flexible graphite composite bipolar plate and a preparation method thereof, belonging to the technical field of high-temperature fuel cell materials. Background Art

[0002] Bipolar plates are an indispensable key component in fuel cell stacks. They are in contact with the membrane electrodes of the anode and cathode on both sides, playing many important roles, such as supporting the membrane electrode structure, separating oxidants and reductants, providing channels, collecting electrons, conducting heat, discharging reaction products, and providing coolant channels. Generally speaking, bipolar plates account for more than 70% of the total mass of the stack and about 30% of the total cost.

[0003] In recent years, with the continuous maturity of high-temperature fuel cell technology and the continuous increase in the design power and power density requirements of the stack, the design of bipolar plates has developed in the direction of larger and thinner. This poses a higher challenge to the materials of bipolar plates. The bipolar plate materials prepared by existing technologies cannot simultaneously meet the requirements of high strength, high toughness, high temperature resistance, and corrosion resistance. Summary of the invention

[0004] Based on the high toughness and corrosion resistance of flexible graphite materials, the present invention develops a new preparation process to improve the bending strength and thermal deformation temperature of the material, which can fully meet the application requirements of high-power high-temperature fuel cell stacks. The present invention provides a high-strength, high-temperature resistant flexible graphite composite bipolar plate and a preparation method thereof, which belongs to the technical field of high-temperature fuel cell materials. Since the carbonization temperature of carbohydrates is almost completely consistent with the expansion temperature of graphite, carbohydrates and expandable graphite are simultaneously expanded to obtain biomass carbon modified expanded graphite. In this process, part of the water released by high-temperature carbonization of carbohydrates participates in the adjustment of the graphite interlayer spacing, and the other part reacts with the graphite surface to produce more functional groups such as hydroxyl and carboxyl groups, which are beneficial to the chemical cross-linking with the impregnating resin in the later stage; the main chain after dehydration is an active CC structure, which interacts with graphite to produce a structural reinforcement effect. This process does not involve any toxic, harmful and polluting substances, is clean, environmentally friendly and low-cost, and the modified expanded graphite is cold-pressed to obtain a preformed plate, and then the bipolar plate product is obtained after resin impregnation and curing. In order to further improve the heat resistance of the bipolar plate, a thermosetting resin with a high cross-linking density is used for impregnation. Therefore, the flexible graphite bipolar plate prepared by the method of the present invention has the characteristics of both high strength and high temperature resistance.

[0005] The present invention provides a high-strength, high-temperature resistant flexible graphite composite bipolar plate. The bipolar plate is firstly prepared by cold pressing a preformed plate from biomass carbon modified expanded graphite obtained by synchronous expansion of expandable graphite and carbohydrates, and then impregnated with a thermosetting resin and then cured and formed; the carbohydrates are selected from one of water-soluble starch and maltose or a mixture of the two.

[0006] Furthermore, in the above technical solution, the thickness of the composite bipolar plate is 0.5-3.5 mm, and the density is 1.6-1.9 g / cm 3 , electrical conductivity is 300~400S / cm, thermal deformation temperature is ≥220℃, and bending strength is ≥60MPa.

[0007] Furthermore, in the above technical solution, the mass ratio of carbohydrate to expandable graphite is 0.005~0.05:1.

[0008] The present invention further provides a method for preparing the above-mentioned bipolar plate, characterized in that it comprises the following steps:

[0009] (1) rinsing expandable graphite in an aqueous solution of a carbohydrate, draining and drying, to obtain a carbohydrate-coated modified expandable graphite;

[0010] (2) placing the carbohydrate-coated modified expandable graphite obtained in step (1) into an expansion furnace for expansion at a temperature of 600 to 950° C. to obtain biomass carbon-modified expandable graphite;

[0011] (3) molding the biomass carbon-modified expanded graphite obtained in step (2) to obtain a preformed electrode plate;

[0012] (4) Prepare a dilute resin impregnation solution and control the viscosity below 350 cP by adjusting the solid content;

[0013] (5) The preformed plate obtained in step (3) is placed in the dilute resin impregnation solution obtained in step (4) for vacuum impregnation, and after cleaning, it is first dried to remove the solvent, and then cured to obtain a finished bipolar plate.

[0014] Furthermore, in the above technical solution, in step (1), the carbohydrate includes one or a mixture of water-soluble starch and maltose.

[0015] Furthermore, in the above technical solution, in step (1), the solid content of the aqueous solution of carbohydrate is 1-10wt%; and the drying temperature is 60-80°C.

[0016] Furthermore, in the above technical solution, in step (1), the mass ratio of carbohydrate to expandable graphite is 0.005-0.05:1.

[0017] Furthermore, in the above technical solution, in step (2), the bulk density of the biomass carbon modified expanded graphite is 0.005-0.01 g / cm 3 .

[0018] Furthermore, in the above technical solution, in step (4), the resin component contained in the dilute resin impregnation liquid is one or a mixture of bismaleimide resin, furan resin, vinyl ester resin, modified vinyl ester resin, phenolic resin, and epoxy resin; the solid content of the dilute resin impregnation liquid is 1 to 10 wt%, and the solvent used is one or a mixture of ethanol, xylene, ethyl acetate, butanone, styrene, dibasic acid ester, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.

[0019] Furthermore, in the above technical solution, in step (5), the vacuum degree of the vacuum impregnation is -0.08 to -0.1 MPa, and the impregnation time is 8 to 12 hours; the drying temperature is 60 to 80°C, and the drying time is 4 to 8 hours; the curing temperature is 150 to 350°C, and the curing time is 30 to 300 minutes.

[0020] The advantages of this application are:

[0021] The present invention proposes a high-strength, high-temperature-resistant flexible graphite composite bipolar plate and a preparation method thereof, using biomass carbon-modified expanded graphite obtained by synchronously expanding biomass-derived carbohydrates and expandable graphite as the main raw material. The raw material preparation process is simple, and the preparation process does not involve any toxic, harmful or polluting substances, which is clean, environmentally friendly and low-cost. The impregnation process uses a thermosetting resin with a high cross-linking density to further improve the strength and heat resistance of the product. The finished bipolar plate can simultaneously have the characteristics of high strength, high toughness, high temperature resistance and corrosion resistance, fully meeting the application requirements of high-power high-temperature fuel cell stacks. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the modified expanded graphite roller preforming method;

[0023] Figure 2 This is a schematic diagram of the finished bipolar plate. DETAILED DESCRIPTION

[0024] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0025] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0026] Example 1

[0027] A high-strength, high-temperature resistant flexible graphite composite bipolar plate is prepared according to the following steps:

[0028] (1) Add maltose to water and stir thoroughly to prepare a rinse solution with a solid content of 10%, add expandable graphite to the rinse solution, stir slowly for 20 minutes, drain with filter cloth, and place in a forced air oven to dry at 75° C. for 6 hours to obtain modified expandable graphite;

[0029] (2) The modified expandable graphite obtained in step (1) is placed in an expansion furnace and expanded at 800°C to obtain biomass carbon modified expanded graphite, which is then rolled to a density of 0.1 g / cm 3 , 7.5 mm thick plate, use a die cutter to punch the plate into a flat prefabricated bipolar plate, see Figure 1 ;

[0030] (3) 15 g of commercially available phenolic epoxy modified vinyl ester resin (SWANCOR 977-S) with a solid content of 70% was added to 185 g of styrene liquid for dilution, and after sufficient stirring, a dilute resin impregnation solution with a solid content of 5.25% was obtained;

[0031] (4) Pour the dilute resin impregnation liquid obtained in step (3) into a small flat tray with a liquid level of 15 mm (not less than 2 times the thickness of the prefabricated board). Place the prefabricated board obtained in step (2) on the surface of the impregnation liquid. The prefabricated board should be in a floating state. Place the tray containing the impregnation liquid and the prefabricated board in a vacuum oven and evacuate the air. Maintain the vacuum degree at -0.08~-0.1MPa and immerse for 4 hours. At this time, the prefabricated board sinks to the bottom layer of the impregnation liquid. After returning to normal pressure, let it stand for 2 hours before taking out the sample. Use ethyl acetate to rinse off the residual resin on the surface of the sample and place it in an oven with exhaust gas treatment to dry the solvent. The drying temperature is 75°C and the drying time is 6 hours. After drying, the impregnated prefabricated board is obtained;

[0032] (5) Place the impregnated prefabricated plate obtained in the previous step into a mold for hot pressing and curing. Keep it at 160°C and 15MPa for 45 minutes and then stop heating. When the mold cools to below 80°C, release the pressure and open the mold to obtain the finished plate. Figure 2 .

[0033] Performance test: According to "GB / T 1634.1-2004 Determination of thermal deformation temperature of plastics under load", the heat deformation temperature of the bipolar plate is 221°C; according to "GB / T 9341-2008 Determination of bending properties of plastics", the bending strength of the bipolar plate is 63MPa; according to "GB / T 20042.6-2024 Proton exchange membrane fuel cell Part 6: Bipolar plate characteristics test method", the conductivity of the bipolar plate is 352S / cm.

[0034] Example 2

[0035] A high-strength, high-temperature resistant flexible graphite composite bipolar plate is prepared according to the following steps:

[0036] (1) adding water-soluble starch to water and stirring thoroughly to prepare a rinse solution with a solid content of 7.5%, placing expandable graphite into the rinse solution and slowly stirring for 20 minutes, then draining with a filter cloth, placing in a forced air oven and drying at 80° C. for 6 hours to obtain modified expandable graphite;

[0037] (2) The modified expandable graphite obtained in step (1) is placed in an expansion furnace and expanded at 850°C to obtain biomass carbon modified expanded graphite, which is then rolled to a density of 0.08 g / cm 3 , and a plate with a thickness of 7.5 mm, and then using a die cutter to punch the plate into a flat prefabricated bipolar plate;

[0038] (3) adding 15 g of bismaleimide resin into 185 g of NMP and dissolving it fully to obtain a dilute resin impregnation solution with a solid content of 7.5%;

[0039] (4) Pour the dilute resin impregnation liquid obtained in step (3) into a small flat tray with a liquid level of 15 mm (not less than 2 times the thickness of the prefabricated board). Place the prefabricated board obtained in step (2) on the surface of the impregnation liquid. The prefabricated board should be in a floating state. Place the tray containing the impregnation liquid and the prefabricated board in a vacuum oven and evacuate the air. Maintain the vacuum degree at -0.08~-0.1MPa and immerse for 6 hours. At this time, the prefabricated board sinks to the bottom layer of the impregnation liquid. After returning to normal pressure, let it stand for 2 hours before taking out the sample. Use ethyl acetate to rinse off the residual resin on the surface of the sample and place it in an oven with exhaust gas treatment to dry the solvent. The drying temperature is 120°C and the drying time is 6 hours. After drying, the impregnated prefabricated board is obtained;

[0040] (5) The impregnated prefabricated plate obtained in the previous step is placed in a mold for hot pressing and curing. The temperature is first adjusted to 120°C and then pressurized. After the pressure reaches 5 MPa, the temperature is raised to 180°C. The pressure is continued to be increased to 15 MPa and then maintained. At this time, the temperature is raised to 300°C and maintained for 30 minutes, then lowered to 260°C, and continued to be maintained for 180 minutes before stopping heating. When the mold is cooled to below 120°C, the pressure is released and the mold is opened to obtain the finished plate.

[0041] Performance test: According to "GB / T 1634.1-2004 Determination of heat deformation temperature of plastics under load", the heat deformation temperature of the bipolar plate is 237°C; according to "GB / T 9341-2008 Determination of bending properties of plastics", the bending strength of the bipolar plate is as high as 86MPa; according to "GB / T 20042.6-2024 Proton exchange membrane fuel cell Part 6: Bipolar plate characteristics test method", the conductivity of the bipolar plate is 333S / cm.

[0042] Comparative Example 1

[0043] A flexible graphite composite bipolar plate is prepared according to the following steps:

[0044] (1) putting expandable graphite into deionized water and slowly stirring for 20 min, then draining with filter cloth, and drying in a forced air oven at 75° C. for 6 h to obtain treated expandable graphite;

[0045] (2) The expandable graphite obtained in step (1) is placed in an expansion furnace and expanded at 800°C to obtain expanded graphite, which is then rolled to a density of 0.1 g / cm 3 , and a plate with a thickness of 7.5 mm, and then using a die cutter to punch the plate into a flat prefabricated bipolar plate;

[0046] (3) 15 g of commercially available phenolic epoxy modified vinyl ester resin (SWANCOR 977-S) with a solid content of 70% was added to 185 g of styrene liquid for dilution, and after sufficient stirring, a dilute resin impregnation solution with a solid content of 5.25% was obtained;

[0047] (4) Pour the dilute resin impregnation liquid obtained in step (3) into a small flat tray with a liquid level of 15 mm (not less than 2 times the thickness of the prefabricated board). Place the prefabricated board obtained in step (2) on the surface of the impregnation liquid. The prefabricated board should be in a floating state. Place the tray containing the impregnation liquid and the prefabricated board in a vacuum oven and evacuate the air. Maintain the vacuum degree at -0.08~-0.1MPa and immerse for 4 hours. At this time, the prefabricated board sinks to the bottom layer of the impregnation liquid. After returning to normal pressure, let it stand for 2 hours before taking out the sample. Use ethyl acetate to rinse off the residual resin on the surface of the sample and place it in an oven with exhaust gas treatment to dry the solvent. The drying temperature is 75°C and the drying time is 6 hours. After drying, the impregnated prefabricated board is obtained;

[0048] (5) The impregnated prefabricated plate obtained in the previous step is placed in a mold for hot pressing and curing. The temperature is maintained at 160°C and 15 MPa for 45 minutes and then the heating is stopped. When the mold is cooled to below 80°C, the pressure is released and the mold is opened to obtain a finished plate.

[0049] Performance test: The heat deformation temperature of the bipolar plate tested according to "GB / T 1634.1-2004 Determination of heat deformation temperature of plastics under load" is 214°C, the bending strength of the bipolar plate tested according to "GB / T 9341-2008 Determination of bending properties of plastics" is 47MPa, and the conductivity of the bipolar plate tested according to "GB / T 20042.6-2024 Proton exchange membrane fuel cell Part 6: Bipolar plate characteristic test method" is 358S / cm. Compared with Example 1, the heat deformation temperature and bending strength of the bipolar plate are significantly reduced by replacing the biomass carbohydrate rinse with deionized water, but the conductivity does not change much, indicating that the introduction of biomass carbohydrates improves the structural density of the composite material, but hardly affects the conductivity of the material.

[0050] Comparative Example 2

[0051] A flexible graphite composite bipolar plate is prepared according to the following steps:

[0052] (1) Sodium carboxymethyl cellulose is added to water and stirred thoroughly to prepare a rinse solution with a solid content of 10%, expandable graphite is added to the rinse solution and stirred slowly for 20 minutes, then drained with a filter cloth, and placed in a forced air oven and dried at 75° C. for 6 hours to obtain modified expandable graphite;

[0053] (2) The modified expandable graphite obtained in step (1) is placed in an expansion furnace and expanded at 800°C to obtain biomass carbon modified expanded graphite, which is then rolled to a density of 0.1 g / cm 3 , and a plate with a thickness of 7.5 mm, and then using a die cutter to punch the plate into a flat prefabricated bipolar plate;

[0054] (3) 15 g of commercially available phenolic epoxy modified vinyl ester resin (SWANCOR 977-S) with a solid content of 70% was added to 185 g of styrene liquid for dilution, and after sufficient stirring, a dilute resin impregnation solution with a solid content of 5.25% was obtained;

[0055] (4) Pour the dilute resin impregnation liquid obtained in step (3) into a small flat tray with a liquid level of 15 mm (not less than 2 times the thickness of the prefabricated board). Place the prefabricated board obtained in step (2) on the surface of the impregnation liquid. The prefabricated board should be in a floating state. Place the tray containing the impregnation liquid and the prefabricated board in a vacuum oven and evacuate the air. Maintain the vacuum degree at -0.08~-0.1MPa and immerse for 4 hours. At this time, the prefabricated board sinks to the bottom layer of the impregnation liquid. After returning to normal pressure, let it stand for 2 hours before taking out the sample. Use ethyl acetate to rinse off the residual resin on the surface of the sample and place it in an oven with exhaust gas treatment to dry the solvent. The drying temperature is 75°C and the drying time is 6 hours. After drying, the impregnated prefabricated board is obtained;

[0056] (5) The impregnated prefabricated plate obtained in the previous step is placed in a mold for hot pressing and curing. The temperature is maintained at 160°C and 15 MPa for 45 minutes and then the heating is stopped. When the mold is cooled to below 80°C, the pressure is released and the mold is opened to obtain a finished plate.

[0057] Performance test: According to "GB / T 1634.1-2004 Determination of thermal deformation temperature of plastics under load", the heat deformation temperature of the bipolar plate is 203°C; according to "GB / T 9341-2008 Determination of bending properties of plastics", the bending strength of the bipolar plate is 38MPa; according to "GB / T 20042.6-2024 Proton exchange membrane fuel cell Part 6: Bipolar plate characteristic test method", the conductivity of the bipolar plate is 294S / cm.

[0058] Compared with Example 1, when sodium carboxymethyl cellulose was used instead of maltose to prepare the rinse solution, the heat deformation temperature, bending strength and conductivity of the bipolar plate were greatly reduced, indicating that not all carbohydrates can improve the performance of flexible graphite bipolar plates.

[0059] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a high-strength, high-temperature resistant flexible graphite composite bipolar plate, characterized in that: The bipolar plate is firstly prepared by cold pressing a preformed plate from biomass carbon modified expanded graphite prepared by simultaneous expansion of expandable graphite and carbohydrate, and then impregnated with a thermosetting resin and cured to form the preformed plate; the carbohydrate is selected from one of water-soluble starch and maltose or a mixture of the two; The thickness of the composite bipolar plate is 0.5-3.5 mm, and the density is 1.6-1.9 g / cm 3 , electrical conductivity is 300~400S / cm, thermal deformation temperature is ≥220℃, bending strength is ≥60MPa; The preparation method comprises the following steps: (1) rinsing expandable graphite in an aqueous solution of a carbohydrate, draining and drying, to obtain a carbohydrate-coated modified expandable graphite; (2) placing the carbohydrate-coated modified expandable graphite obtained in step (1) into an expansion furnace for expansion at a temperature of 600 to 950° C. to obtain biomass carbon-modified expandable graphite; (3) molding the biomass carbon-modified expanded graphite obtained in step (2) to obtain a preformed electrode plate; (4) Prepare a dilute resin impregnation solution and control the viscosity below 350 cP by adjusting the solid content; (5) The preformed plate obtained in step (3) is placed in the dilute resin impregnation solution obtained in step (4) for vacuum impregnation, and after cleaning, it is first dried to remove the solvent, and then cured to obtain a finished bipolar plate.

2. The preparation method according to claim 1, characterized in that: In step (1), the solid content of the carbohydrate aqueous solution is 1-10 wt % and the drying temperature is 60-80° C.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of carbohydrate to expandable graphite is 0.005-0.05:

1.

4. The preparation method according to claim 1, characterized in that: In step (2), the bulk density of the biomass carbon modified expanded graphite is 0.005-0.01 g / cm 3 .

5. The preparation method according to claim 1, characterized in that: In step (4), the resin component contained in the dilute resin impregnation liquid is one or a mixture of bismaleimide resin, furan resin, vinyl ester resin, modified vinyl ester resin, phenolic resin, and epoxy resin; the solid content of the dilute resin impregnation liquid is 1 to 10 wt %, and the solvent used is one or a mixture of ethanol, xylene, ethyl acetate, butanone, styrene, dibasic acid ester, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.

6. The preparation method according to claim 1, characterized in that: In step (5), the vacuum degree of the vacuum impregnation is -0.08 to -0.1 MPa, and the impregnation time is 8 to 12 hours; the drying temperature is 60 to 80°C, and the drying time is 4 to 8 hours; the curing temperature is 150 to 350°C, and the curing time is 30 to 300 minutes.

Citation Information

Patent Citations

  • Preparation method of flexible composite bipolar plate and fuel cell

    CN117855511A

  • Process for the production of mouldings

    US5288429A